Steroidogenic enzyme gene expression and testosterone production are developmentally modulated by bone morphogenetic protein receptor-1B in mouse testis - Ciller, I; Palanisamy, S; Ciller, U; Al-Ali, I; Coumans, J; McFarlane, J (Physiological research, 2023)
Bone morphogenetic proteins (BMPs) and receptors (BMPR-1A, BMPR-1B, BMPR-2) have been shown to be vital for female reproduction, while their roles in males are poorly described. Our study was undertaken to specify the function of BMPR-1B in steroidogenic enzyme gene expression, testosterone production and reproductive development in male mice, given that Bmpr1b mRNA is expressed in mouse testis and Bmpr1b knockout results in compromised fertility. Male mice were passively immunized for 6 days with anti-BMPR-1B in the presence or absence of exogenous gonadotrophins. We then measured the effects of anti-BMPR-1B on testicular hydroxysteroid dehydrogenase isoforms (Hsd3b1, Hsd3b6, and Hsd17b3) and aromatase (Cyp19) mRNA expression, testicular and serum testosterone levels, and testis and seminal vesicle weight. In vitro testosterone production in response to anti-BMPR-1B was determined using testicular culture, and Leydig cell culture in the presence or absence of gonadotrophins. In Leydig cell culture the contribution of seminiferous tubules and Leydig cells were examined by preconditioning the media with these testicular constituents. In adult mice, anti-BMPR-1B increased testosterone and Hsd3b1 but decreased Hsd3b6 and Cyp19 mRNA. In adult testicular culture and seminiferous tubule conditioned Leydig cell culture, anti-BMPR-1B reduced testosterone, while in normal and Leydig cell conditioned Leydig cell culture it increased testosterone levels. In pubertal mice, anti-BMPR-1B reduced gonadotrophin stimulated seminal vesicle growth. In conclusion, BMPR-1B has specific developmental functions in the autocrine and paracrine regulation of testicular steroidogenic enzyme gene expression and testosterone production in adults and in the development of seminal vesicles during puberty.
Keywords: exprese genu; testis; messenger RNA; Gene Expression; Sexual Maturation; Female; zvířata; myši; kostní morfogenetické proteiny; Mice; RNA, Messenger; ženské pohlaví; Bone Morphogenetic Proteins; receptory kostního morfogenetického proteinu; Male; Testosterone; Testis; Bone Morphogenetic Protein Receptors; pohlavní dospělost; Aromatase; Animals; aromatasa; mužské pohlaví; testosteron